The Geopolitical Implications of Infrastructure Development and Trade Roads in International Relations - Dr. Pritee Verma (Research Parks Publishers, 2022)
A trade road is a logistical network identified as a series of pathways and stoppages used for the commercial transport of cargo. The term can also be used to refer to trade over bodies of water. Allowing goods to reach distant markets, a single trade route contains long-distance arteries, which may further be connected to smaller networks of commercial and noncommercial transportation roads. Among notable trade roads was the Amber Road, which served as a dependable network for long-distance trade.[1] Maritime trade along the Spice Route became prominent during the Middle Ages, when nations resorted to military means for control of this influential route.[2] During the Middle Ages, organizations such as the Hanseatic League, aimed at protecting interests of the merchants and trade became increasingly prominent.[3] In modern times, commercial activity shifted from the major trade roads of the Old World to newer roads between modern nation-states. This activity was sometimes carried out without traditional protection of trade and under international free-trade agreements, which allowed commercial goods to cross borders with relaxed restrictions.[4] Innovative transportation of modern times includes pipeline transport and the relatively well-known trade involving rail roads, automobiles, and cargo airlines.